O dia é da rua, a noite é do albergue: condições e contradições de um abrigo de regime aberto para adolescentes em situação de rua na cidade de Fortaleza. - Ferreira, Diocleide Lima (2000)
This study aims to analyze the process of socialization of adolescents in "homeless" in the city of Fortaleza. The place of research is the Hostel 01, core activities within the Campus Service Center for children and adolescents, working with the Foundation for Welfare of Minors in the state of Ceará (FEBEMCE). This hostel is a place regarded as home of the open, that is, a shelter that brings children and adolescents living in the streets of Fortaleza, and is referred to the Child and Adolescent (ECA) as a Measure to Protect who are "homeless" as well as for those who leave schemes socio-educational semi-closed and open. The group of teens who worked in particular, were teenagers who stemmed the socio-educational schemes closed and semi-open, being framed as offenders, not discarding those that were completely out of this profile. The research was conducted between the years 1997 to 2000. And the methodology used in this intercourse was participant observation in all activities directed at adolescents, as I assign resources such as interviews with teens, educators, psychologists and police officers on duty there. Also make use of research in the archives of Hostel 1, especially in the monitoring reports of adolescents. The dissertation was prepared in the form of a somewhat dense description of the moments experienced in Hostel 1 with individuals who, because of the violence of the Brazilian state, built a path of institutionalization, and "sustained" and at the same time, "violated" by that State. And even with the arrival of the ECA, their life histories are still overtake the reproduction of social values tense and charged with disbelief. The categories of analysis: re-socialization, citizenship, rights, silence, work, risk, stigma, institutionalization and differentiation guide the writing of this description, which, driven by more general theme of violence, show the reordering of policies aimed at assisting children and adolescents in Brazil since the early 1990s.